Prediction of Survival Benefit of Filgrastim in Adult and Pediatric Patients With Acute Radiation Syndrome - John Harrold; Per Olsson Gisleskog; Juan Jose Perez‐Ruixo; Isabelle Delor; Andrew Chow; Philippe Jacqmin; Murad Melhem (Wiley, 2020)
Acute exposure to high doses of radiation leads to severe myelosuppression, but few treatments are currently available to treat hematopoietic syndrome of acute radiation syndrome. Granulocyte colony stimulating factors (e.g., filgrastim) stimulate proliferation of neutrophil precursors and enhance mature neutrophil function. Owing to ethical constraints on conducting clinical research in lethally irradiated humans, we developed a model‐based strategy to integrate preclinical experience in irradiated nonhuman primates (NHPs) and other clinical myelosuppressive conditions to inform filgrastim dosing to treat hematopoietic syndrome of acute radiation syndrome. Models predicting neutrophil counts and overall survival based on drug exposures were calibrated and scaled from NHPs to adult and pediatric human subjects. Several scenarios were examined investigating variations in filgrastim doses, dose frequency, treatment initiation, and duration, as well as the effect of age and radiation dose rate. Model‐based simulations and established safety profiles supported that a subcutaneous filgrastim dose of 10 µg/kg once daily provides a significant survival benefit (50%) over placebo in both adults and children, provided that the treatment is initiated within 1-14 days after radiation exposure and lasts 2-3 weeks. For treatment durations of longer than 3 weeks, filgrastim treatment is not expected to provide significantly greater benefit. This survival benefit is expected to hold for the wide range of radiation doses and dose rates (0.01-1,000 Gy/hours) examined.